A profile of financial incentives to work in Ireland - Savage, Michael; Callan, Tim; Walsh, John R. (Statistical and Social Inquiry Statistical Society of Ireland, 2015)
Tax and benefit systems have to strike a balance between the goals of providing an adequate safety-net income to those who need it and maintaining adequate incentives to take up employment and to increase earnings. Ireland has seen substantial changes to direct taxes, and in welfare payments, during recent years. The implications for income distribution are examined in a separate paper. In this paper we take stock of the implications for the structure of financial incentives to work in Ireland, using SWITCH, the ESRI tax-benefit model We look at two key aspects of labour supply: financial incentives to take up or remain in employment – commonly measured by replacement rates - and financial incentives to move from part-time to full-time employment – measured by marginal effective tax rates, which take account of the withdrawal of benefits as well as explicit direct taxes. We analyse the characteristics of the individuals or households most likely to face strong financial disincentives to work.
(read before the Society, 15th April 2015)
Keywords: taxation; welfare; employment; income; Ireland; 314.15